A follow-up program in patients after hospitalization for heart failure: long-term health related quality of life and associated factors - Paleckiene, R.; Zaliaduonyte, D.; Dambrauskiene, V.; Macijauskiene, J. (Frontiers in Cardiovascular Medicine, 2024)
Background The well-being of individuals with chronic heart failure (HF) is significantly influenced by their health-related quality of life (HRQoL), which serves as a crucial measure indicating how HF affects their daily activities. Monitoring programs aimed at reducing the number of hospitalizations and improving functional conditions are currently being offered to patients with chronic HF. The objective To examine the long-term health-related quality of life changes in patients with heart failure enrolled in a follow-up program after hospitalization and to evaluate the factors associated with quality of life of patients with heart failure. Methods This prospective study was conducted between 2019 and 2020 at the Department of Cardiology of Lithuanian University of Health Sciences. Patients were divided into two groups: Group I consisted of 71 patients (60.2%) where the Minnesota Living with Heart Failure Questionnaire (MLHFQ) score decreased by more than 10 points at 4th visit if compared to the 1st one; and Group II consisted of 47 patients (39.8%) where the MLHFQ score remained unchanged or increased by less than 10 points at the 4th visit if compared to the 1st visit. Results Statistically significant differences were observed between groups. In Group II, a history of myocardial infarction was more frequent (p = 0.038), and there was a significantly higher occurrence of significant coronary artery disease (p = 0.006). Laboratory parameters indicating liver function exhibited statistically significant deterioration among patients in Group II. Specifically, AST (p = 0.050), ALT (p = 0.010), and GGT (p = 0.031) levels significantly increased. Upon analyzing the echocardiographic data, a statistically significant difference was found between the groups in relation to the left ventricular ejection fraction (LVEF) (p = 0.043) and TAPSE (p = 0.031). An analysis of changes in dimensions related to QoL was conducted during the long-term follow-up program, which revealed statistically significant differences between groups in overall changes based on the MLHFQ (p < 0.001). This difference was also observed across all dimensions, including the emotional, physical, and social aspects (p < 0.001). Conclusion Patients who had a higher LVEF at baseline, as well as those with an etiology of ischemic heart disease (IHD), better liver function, and fewer manifestations of edema, demonstrated a statistically significant improvement in their quality of life throughout the course of the patient monitoring program.